NEBUCHADNEZZAR AND ALEXANDER IN THE EXCERPTA LATINA BARBARI. (2nd March 2016) - Garstad, Benjamin
Abstract : The late antique Christian chronicle preserved as the Excerpta Latina Barbari contains a brief, but extraordinary notice on the Babylonian king Nebuchadnezzar; many of its unusual details can be understood in the contexts of traditional stories about Nebuchadnezzar and the interests of the work itself. The best clue to the meaning of the passage on Nebuchadnezzar is the Excerpta 's closely parallel passage on Alexander the Great. In the Excerpta Nebuchadnezzar and Alexander reflect one another and in a sense compete with one another. Many of the odd details of the notice on Nebuchadnezzar can be explained as directing the reader toward this parallelism. The parallelism itself seems to serve two purposes. First, to provide symmetry to the Excerpta 's idiosyncratic account of world history in which Alexander liberates the world conquered by Nebuchadnezzar. And second, to show Nebuchadnezzar subtly outdoing Alexander, so that Alexander's encounter with the God of the Jews, as it is found in the Excerpta, can be provided with an implicit interpretation and characterization.